The effect of crop rotation on the soil biological activity - S. А. Zamyatin; R. В. Maksimova (Зерновое хозяйство России, 2021)
The current paper has presented the results of long-term experiments on the study of the biological activity of sod-podzolic soil by the application method in field crop rotations. The experimental part of the work was carried out on the experimental plots of the Mari Research Institute of Agriculture, a branch of the FSBSI FARC of the North-East in 1996–2020. The trials were laid down in 1996 and 1998. The trial was laid down in two factors. Factor A included such types of crop rotations as grain-grasses crop rotations (oats + clover, clover of 1 year of use, winter crops, vetch-oat mixture for grain, spring wheat, barley as a control grain crop); the first rotation of crops (annual leguminous grasses, winter crops, barley, potatoes, vetch-oat mixture for grain, spring wheat); the second rotation of crops (vetch-oat mix[1]ture for grain, spring wheat, potatoes fertilized with manure (80 t/ha), barley + clover, clover of 1 year of use, winter crops); the third rotation of crops (barley + clover, clover of 1 year of use, clover of 2 years of use, winter crops, pota[1]toes, oats). Factor B included application of mineral fertilizers: control grain crop (without fertilizers); N60P60K60. There has been established that the activity of soil microflora mainly depended on the presence of organic matter in the soil. The largest activity of cellulose-destroying microorganisms against a natural background of fertility was identified in the second rotation of crops, with the introduction 23.9% of manure for potatoes in the first period (45 days) and 54.7% in the second period (90 days) of exposure. The slightest biological activity of the soil was identified in the grain-grasses crop rotation (with 83% of grain crops); it was 17.7% in the first 45 days and 43.4% in the second period of exposure. That was caused by the deficit of organic matter. The introduction of mineral fertilizers in a dose of N60P60K60 under pre-sowing tillage significantly increased the soil biological activity in comparison to the unfertilized background, and a fairly high intensity of flax decomposition was observed in the second rotation of crops with 24.9% in 45 days and 56.8% in 90 days. Correlation analysis (1998-2019) between the mean flax decomposition under crops for the entire vegetation period and the value of the hydrothermal coefficient (HThC) showed a close direct correlation, which in the first and second periods of exposure was 0.87–0.90 and 0.86–0.89, respectively.